2008
DOI: 10.4319/lo.2008.53.1.0160
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove tannins in aquatic ecosystems: Their fate and possible influence on dissolved organic carbon and nitrogen cycling

Abstract: We describe the fate of mangrove leaf tannins in aquatic ecosystems and their possible influence on dissolved organic nitrogen (DON) cycling. Tannins were extracted and purified from senescent yellow leaves of the red mangrove (Rhizophora mangle) and used for a series of model experiments to investigate their physical and chemical reactivity in natural environments. Physical processes investigated included aggregation, adsorption to organic matter-rich sediments, and co-aggregation with DON in natural waters. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 51 publications
4
74
1
Order By: Relevance
“…Since the fluorescence characteristics of component 4 were similar to those of tannins (Maie et al 2007(Maie et al , 2008 as well as to a blue-shifted tryptophan-like fluorophore (Maie et al 2006), it is difficult to determine the precise origin of component 4 based only on the fluorescence characteristics. However, the relationship with salinity as well as the transect distribution of component 4 were almost identical to those of component 5 (Figs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the fluorescence characteristics of component 4 were similar to those of tannins (Maie et al 2007(Maie et al , 2008 as well as to a blue-shifted tryptophan-like fluorophore (Maie et al 2006), it is difficult to determine the precise origin of component 4 based only on the fluorescence characteristics. However, the relationship with salinity as well as the transect distribution of component 4 were almost identical to those of component 5 (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Tryptophan-like fluorophores shifted to shorter emission wavelength were also found concurrently with tyrosine-like fluorophores in the ultrafiltered DOM of the Florida coastal Everglades (Maie et al 2006). In addition to aromatic amino acid residues in DOM, polyphenols such as galic acids and tannins exhibited such fluorescence characteristics (Maie et al 2007). The fluorescence characteristics of component 4 were also similar to those of tannins, showing a peak at excitation/emission of 275/ 313 nm (Maie et al 2007(Maie et al , 2008.…”
Section: Resultsmentioning
confidence: 99%
“…Sarpal et al (1995) suggested that the shoulder on the absorption spectrum at 280-290 nm was caused in part by proteins. In addition to proteins, other bio-components have absorption mostly at wavelengths shorter than 300 nm (Zika 1981;Maie et al 2007Maie et al , 2008.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, the increase in nitrogen concentrations in leaf litter may be due to greater loss of carbon and mass than nitrogen, and on the other hand, the immobilization of external nitrogen, such as microbial biomass (He et al 1988, Wang et al 2012) and dissolved organic nitrogen (Maie et al 2008), and internal nitrogen, such as leaf litter protein and amino acids (Gallardo and Merino 1992). We observed a negative correlation between TP and nitrogen contents at various stages of decay (Table 1), which is indicative of humification reactions.…”
Section: Resultsmentioning
confidence: 99%